Evaluation of the effect of signalment and owner-reported impairment level on accelerometer-measured changes in activity in osteoarthritic dogs receiving a non-steroidal anti-inflammatory. (December 2018) - Muller, C.; Gines, J.A.; Conzemius, M.; Meyers, R.; Lascelles, B.D.X.
Highlights: Higher impairment is significantly associated with larger NSAID-treatment related positive changes in activity. Impairment level should be controlled for in clinical trials involving dogs with osteoarthritis. Using higher impaired dogs may result in greater treatment effects, increasing the power of the study Abstract: In veterinary medicine, evaluation of osteoarthritis (OA) treatment efficacy remains challenging. Measurement of activity, utilizing accelerometers, provides a surrogate measure of pain through measuring effects on activity, and the objective data collected can be used to assess the efficacy of treatments. However, little is known about how dog characteristics impact the accelerometry-measured response to treatment. The objectives of this study were to evaluate the effect of signalment and initial impairment level on accelerometer-measured changes in activity in osteoarthritic dogs after receiving a non-steroidal anti-inflammatory (NSAID). Fifty-seven client-owned dogs with OA-associated pain and mobility impairment were administered meloxicam for 2 weeks, following a 2-week baseline, and spontaneous activity was measured using an Actical accelerometer unit. Signalment factors and disease variables were recorded (age, sex, weight, impairment level, forelimb or hindlimb pain). Initial degree of impairment had a significant effect on changes in weekly ( P  = 0.009), weekday ( P   =  0.044) activity following NSAID treatment. Greater initial impairment was associated with larger positive changes in activity. Degree of impairment should be taken into consideration during the development of a clinical trial. Appropriate selection of candidates based on initial degree of impairment may permit a greater treatment effect, therefore increasing the power of the study.